2021
DOI: 10.1186/s12866-020-02078-x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis revealed a wide distribution of antibiotic resistance genes and biosynthesis of antibiotics in the gut of giant pandas

Abstract: Background The gut microbiome is essential for the host’s health and serves as an essential reservoir of antibiotic resistance genes (ARGs). We investigated the effects of different factors, including the dietary shifts and age, on the functional characteristics of the giant panda’s gut microbiome (GPs) through shotgun metagenome sequencing. We explored the association between gut bacterial genera and ARGs within the gut based on network analysis. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Both the number and the diversity of ARGs increased with age, suggesting a higher risk of bacterial resistance to antibiotics in old pandas. Our results were consistent with previous metagenome studies on giant pandas ( 23 , 91 , 92 ). In particular, we found that the proportion of ARGs belonging to fluoroquinolone, tetracycline, and macrolides antibiotics was high in all giant panda fecal samples.…”
Section: Discussionsupporting
confidence: 93%
“…Both the number and the diversity of ARGs increased with age, suggesting a higher risk of bacterial resistance to antibiotics in old pandas. Our results were consistent with previous metagenome studies on giant pandas ( 23 , 91 , 92 ). In particular, we found that the proportion of ARGs belonging to fluoroquinolone, tetracycline, and macrolides antibiotics was high in all giant panda fecal samples.…”
Section: Discussionsupporting
confidence: 93%
“…In the conservation of natural world heritage, the giant panda is widely recognized as a crucial flagship species ( Zhu D. et al, 2021 ). The gut microbiota plays a vital role in the growth, development, and immune processes of giant pandas ( Zhu et al, 2011 ; Zhang et al, 2018 ; Zhu et al, 2018 ; Zhao et al, 2021 ) and is significantly influenced by various factors including diet, phylogeny, seasons, and habitat environment ( Zhang et al, 2018 ; Tang et al, 2020 ; Hu et al, 2021 ; Mustafa et al, 2021 ; Huang et al, 2022 ). Despite the successful downgrading of the conservation status of giant pandas from endangered to vulnerable ( Guo et al, 2019 ), their health and survival are threatened by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug resistance to many different classes of antibiotics, which impedes antibiotic treatment, is a huge risk to human life (Zhu et al, 2013;Ouyang et al, 2015), and is also a potential threat to giant panda health. Several recent studies have shown that diverse ARGs exist in the gut of wild and captive giant pandas, and multidrug resistance genes were the dominant type of ARGs in the giant panda gut (Guo et al, 2019;Hu et al, 2020;Mustafa et al, 2021;. A survey based on ARGs of human gut microbiota in three countries (China, Denmark, and Spain) found that tetracycline resistance genes were the most abundant group of ARGs, followed by MLSs and beta_lactam resistance genes (Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%